What Are The Lived Experiences Of Patients With Cancer And Their Families In Northern Ghana? A Qualitative Study Using Narrative Interview And Creative Task Approach. - Tuck, C.Z.; Akparibo, R.; Gray, L.A.; Suraj, H.; Iddrisu, A.T.; Abane, T.R.; et al. (BMJ Open, 2025)
Objectives: Cancer poses a major burden in Ghana that is exacerbated by poor engagement with biomedical treatment. The reasons for this are not well understood for most cancers and in northern Ghana. Design: This research took combined narrative interviews with a creative task that was analysed through reflexive thematic analysis. Setting: A tertiary treatment centre in northern Ghana. Participants 15 adult (>18 years) patients or their relatives who had been diagnosed and/or treated for cancer within the last 2 years. Results: The thematic analysis highlighted the psychological burden of cancer and ways participants cope and find meaning, including through religion, trust in biomedical treatment, and occupation and social support. The findings stress the negative impact of the financial burden, shame, worry and the spiralling poverty this causes. The creative task was found to be resonant, emotive and more humanising, which is anticipated to be more effective when communicating with policy-makers and community members. The findings provide rich contextual insights to understand patients’ and relatives’ perspectives and frame their experiences within what was important to them. Conclusions: Together the research has identified a critical need for policy to consider the psychosocial, occupational, spiritual and financial needs of patients with cancer in northern Ghana. It has demonstrated narrative interviews with graphical elicitation as an effective approach to discuss sensitive topics for findings that can engage stakeholders and inform holistic cancer service design.
Research Article